The Role of the Notary in the Creation of Subsidized Housing Procurement Agreements between Consumers, Developers, and PT. Bank BTN Mataram Branch - Ricki Akbar; Kurniawan; Eduardus Bayo Sili (International Journal of Global Sustainable Research, 2024)
The objective of this research is to explain and analyze the role of the notary in the creation of subsidized housing procurement agreements between consumers, developers, and PT. Bank BTN Mataram Branch. It also aims to identify the common issues faced by consumers in the process of purchasing subsidized housing through credit. The approach methods used in this study include the Statute Approach, Conceptual Approach, Analytical Approach, and Sociological Approach. The findings are as follows: First, the absence of the notary's role can result in the invalidity and incompleteness of the subsidized housing ownership agreement. Second, without the involvement of a notary, key responsibilities such as verifying the completeness of documents, ensuring compliance with regulationsThe absence of notarial verification on documents like the property ownership certificate, the identity of the parties involved, government permits, and other supporting documents can result in the invalidity of the transaction.Without a notary, the conformity of the agreement with the applicable laws and regulations is not guaranteed, including the examination of the validity requirements according to both positive law and Islamic law. Moreover, without a notary, the formulation of contract clauses that violate regulations related to housing subsidies may occur, jeopardizing the legal certainty and protection of the parties involved.